BAURAN PEMASARAN DAN STRATEGI PENGEMBANGAN PRODUK OLAHAN KOPI ROBUSTA DI KOPERASI TIRTO KENCONO AIR NANINGAN KABUPATEN TANGGAMUS - Melda Riyantika; Ali Ibrahim Hasyim; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the marketing mix and the development strategy of robusta coffee processed products in the Tirto Kencono Air Naningan Cooperative Tanggamus Regency. The research method used is a case study. The analytical method used is descriptive qualitative analysis and SWOT analysis. The marketing mix applied includes good quality robusta coffee products, cash and discounted prices, personal selling promotions, and accessible road to the cooperative. The internal environments consist of products, financial management, human resources, location, and marketing, while the external environments consist of culture, technology, climate and weather, competitors, and government policies. The strategies for developing robusta coffee products in the Tirto Kencono Cooperative are to maintain the quality assurance by utilizing modern technology, to improve skills in marketing by utilizing government support through the given UMKM training, and to implement social media to increase sales volume.Key words: coffee, development strategy, marketing mix